Role of single-particle and pair condensates in Bose systems with arbitrary intensity of interaction - Peletminskii, A.S.; Peletminskii, S.V.; Poluektov, Yu.M. (Condensed Matter Physics, 2013)
We study a superfluid Bose system with single-particle and pair condensates on the basis of a half-phenomenological theory of a Bose liquid not involving the weakness of interparticle interaction. The coupled equations describing the equilibrium state of such system are derived from the variational principle for entropy. These equations are analyzed at zero temperature both analytically and numerically. It is shown that the fraction of particles in the single-particle and pair condensates essentially depends on the total density of the system. At densities attainable in condensates of alkali-metal atoms, almost all particles are in the single-particle condensate. The pair condensate fraction grows with increasing total density and becomes dominant. It is shown that at density of liquid helium, the single-particle condensate fraction is less than 10% that agrees with experimental data on inelastic neutron scattering, Monte Carlo calculations and other theoretical predictions. The ground state energy, pressure, and compressibility are found for the system under consideration. The spectrum of single-particle excitations is also analyzed. Вивчається надплинна бозе-система з одночастинковим та парним конденсатами на основi напiвфеноменологiчної теорiї бозе-рiдини, яка не припускає слабкостi мiжчастинкової взаємодiї. Iз варiацiйного принципу для ентропiї виведено систему рiвнянь, що описують рiвноважний стан такої системи. Цi рiвняння проаналiзовано у випадку нульової температури як аналiтично, так i чисельно. Показано, що частки одночастинкового та парного конденсатiв суттєво залежать вiд повної густини системи. При густинах, що досягаються у конденсатах атомiв лужних металiв, майже всi частинки знаходяться в одночастинковому конденсатi. Доведено, що при густинi рiдкого гелiю частка одночастинкового конденсату є меншою за 10%, що узгоджується з експериментальними даними з непружного нейтронного розсiювання, розрахунками методом Монте-Карло та iншими теоретичними передбаченнями. Знайдено вирази для енергiї основного стану, тиску, стисливостi системи, що вивчається. Проаналiзовано також спектр одночастин-кових збуджень.